If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -6x = 33 + x Solving 3 + -6x = 33 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + -6x + -1x = 33 + x + -1x Combine like terms: -6x + -1x = -7x 3 + -7x = 33 + x + -1x Combine like terms: x + -1x = 0 3 + -7x = 33 + 0 3 + -7x = 33 Add '-3' to each side of the equation. 3 + -3 + -7x = 33 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = 33 + -3 -7x = 33 + -3 Combine like terms: 33 + -3 = 30 -7x = 30 Divide each side by '-7'. x = -4.285714286 Simplifying x = -4.285714286
| 5x+21=12x-29# | | (((x-5)/2)-((2x-5)/3))=(5/6) | | 1/4x-7/8=10-50 | | 25x-29x=8-12 | | 2a+50=5a-4 | | x(x+4)+(x+4)= | | -4x-4x=18-2 | | 15+t=2 | | 3p+5q=36 | | 3x^3+23x-16x^2-6=0 | | A+12=26 | | -54+18=-4x+13x | | 81=9 | | 2(3x+5)+9=3x+34 | | 135=3y | | M/3+m/4=m/4 | | T=3a(ar+h) | | 161=7y | | 5-5=13x+7x | | 6y=114 | | 3n-14=17 | | 2x-10=7x+11 | | -2/5x=-6/25 | | 2x-10=7x+-1 | | 7/4t=-4/7 | | 0.4=-10z | | 4-14=-2z | | 2z=2.3+0.5 | | 22y=440 | | x^2+3xy+y^2=-16 | | 36x+60-14x+49=-2x-31 | | 40=12y-4y |